PENGARUH KETERSEDIAAN KOMPUTER TERHADAP MUTU LULUSAN KOMPETENSI KEAHLIAN USAHA PERJALANAN WISATA DI SMK NEGERI 1 MANADO - Agus Walansendow; Bet El Lagarense; Rein H. Liwutang (Jurnal Ilmu Pariwisata, 2023)
Education sector is a partial effort of improving tourism in Indonesia, because it is education that is expected to produce professional staff in the field of tourism. We can see this from the efforts of the government and the private sector in establishing tourism-related schools, both at the tertiary and high school levels. SMK is an educational institution designed to produce graduates who become middle-class workers in accordance with the demands of the world of work, nationally and globally and thus, their performance needs to be continuously improved so that they can realize quality learning processes and outcomes. This is a formidable challenge for the government, the private sector, and the wider community in general due to the fact that the learning facilities in tourism education are still inadequate, both the teaching staff, textbooks, and other facilities. The purpose of this study was to measure and explain the relationship between the availability of computers as a learning medium and the quality of graduates of the competency skills of the Travel and Tourism Business at SMK Negeri 1 Manado. This study uses a quantitative descriptive method, because in addition to analyzing data with statistical formulas, the authors also want to explain the results of the analysis and interpretation. The method of analysis used is simple linear regression where Variable X is the availability of computers and Variable Y is the quality of graduates' competency expertise in the Travel Business, with correlation coefficient analysis to see the strength and weakness of the relationship between variable X and variable Y. The final results of the study after analyzing the simple linear regression, the correlation coefficient obtained is r = 0.96 indicating that the relationship between computer availability (variable X) and the quality of graduates of Travel Business Skills Competency Travel (variable Y), there is a positive correlation close to 1 and based on the correlation coefficient found 0.96 is included in the very strong category. This means that the availability of computers greatly influences the quality of graduates of the Travel and Tourism Business Skills Competency at SMK Negeri 1 Manado. If the computer owned by SMK Negeri 1 Manado is very good, then automatically the quality of graduates of the Travel and Tourism Business Skills Competency will increase and vice versa. The result of the determinant coefficient (r2) is 0.94 or 94% indicating that there is a 6% change in the variable caused by other factors that are not taken into account.